The correlation of clinical pathway compliance implementation on clinical outcome and sectio caesarian patient costs in a type c private hospital in Lampung - Joko Sunowo; Tri Murti Andayani; Dwi Endarti; Eka Tri Wulandari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Sectio caesaria births are around 17.6% of all births (Riskesdas, 2018), this figure is higher than the figure recommended by WHO. The high incidence and cost of sectio caesaria can cause problems if they are not managed properly. CA clinical pathway (CP) as a multi-disciplinary management plan for patients with certain diagnoses can be used to improve the quality and efficiency of excellent health services for each individual according to the law’s mandate. This research is research (observational analytic) with cross-sectional design and retrospective method for data collection. The data in this research were all BPJS patients who underwent sectio caesaria for the period of 1 January 2020 to 30 June 2020 according to the inclusion and exclusion criteria in a type C private hospital in Lampung Province. The observations were made on CP forms and patient medical record documents as well as details of treatment costs from BPJS claim data. To see the correlation of compliance implementation with CP and clinical outcomes, the Chi-square test was carried out, the average analysis of CP implementation compliance with costs was carried out using a non-parametric regression test, the correlation of confounding variables on clinical outcomes was tested using Chi-square and Somers tests, and the correlation between confounding variables and total real costs was tested using the ANOVA test. The descriptive analysis found that the average CP implementation compliance of 145 patients (63%) had an average good adherence score (more than 85%) and 85 patients (37%) had low adherence (less than 85%). The points of care education and nutrition counseling as well as treatment or medical intervention have the highest score of 99.57% and the lowest is 0.34% in nursing mobilization/rehabilitation. The description of clinical outcomes of 230 patients with sectio caesaria Length of Stay (LOS) according to CP (less than 3 days) as many as 95 patients and 185 patients with pain scale (VAS 2) and no patients had ILO. The results of the statistical analysis showed that there was no correlation of compliance implementation of CP on clinical outcomes based on the pain scale, LOS, and total real costs (p more than 0.05). The result of the statistical analysis of the confounding variables Age (p 0.015) and treatment class (p 0.00) showed that there was a correlation on the total real costs (p less than 0.05). The conclusion of this research is that there is no correlation of compliance implementation with CP on clinical outcomes and the total real cost of sectio caesaria patients, and there is a correlation between age and class of care on the total real cost of sectio caesaria patients.  Abstrak: Kelahiran sectio caesaria sekitar 17, 6% dari seluruh kelahiran  (Riskesdas, 2018), angka ini lebih tinggi dari angka yang direkomendasikan WHO. Tingginya angka kejadian dan biaya sectio caesaria  dapat menimbulkan permasalahan jika tidak dikelola dengan baik. Clinical pathway (CP) sebagai suatu rancangan penatalaksanaan multi disiplin untuk pasien dengan diagnosis tertentu dapat digunakan dalam upaya meningkatkan kualitas dan efisiensi pelayanan kesehatan yang prima kepada setiap individu sesuai amanat Undang Undang. Penelitian ini adalah penelitian (observasional analitik) dengan desain cross sectional dan metode retrospektif untuk pengambilan data. Data pada penelitian ini adalah seluruh pasien BPJS yang menjalani sectio caesaria periode 1 Januari 2020 sampai 30 Juni 2020 sesuai kriteria inklusi dan eksklusi di sebuah RS swasta tipe C di Provinsi Lampung. Pengamatan dilakukan pada form CP dan dokumen rekam medik pasien serta rincian biaya perawatan dari data klaim BPJS. Untuk melihat hubungan kepatuhan pelaksanaan CP terhadap outcome klinik dilakukan uji Chi square, analisis rata-rata kepatuhan pelaksanaan CP terhadap biaya dilakukan menggunakan uji regresi non parametrik , hubungan variable perancu terhadap outcome  klinik diuji menggunakan uji Chi square dan somers serta hubungan variable perancu terhadap total biaya riil diuji menggunakan uji anova. Analisis deskriptif didapatkan, rata-rata kepatuhan pelaksanaan CP sebanyak 145 pasien (63%) memiliki nilai rata-rata kepatuhan baik (85%) dan 85 pasien (37%) untuk kepatuhan rendah (kurang dari 85%). Poin asuhan edukasi dan konseling gizi serta tatalaksana atau intervensi medis memiliki nilai tertinggi sebesar 99,57% dan terendah sebesar 0,34% pada mobilisasi / rehabilitasi keperawatan. Deskripsi outcome klinik dari 230 pasien sectio caesaria Length of Stay (LOS) sesuai CP (kurang dari 3hari) sebanyak 95 pasien dan 185 pasien dengan skala nyeri (VAS 2) serta tidak didapati pasien yang mengalami ILO.  Hasil analisis statistik menunjukkan tidak adanya hubungan kepatuhan pelaksanaan CP terhadap outcome  klinik yang berdasarkan skala nyeri, LOS,dan total biaya riil  (p lebih dari 0,05 ). Hasil analisis statistik variable perancu usia (p 0,015) dan kelas perawatan (p 0,00) menunjukan ada hubungan terhadap total biaya riil  (p kurang dari 0,05). Kesimpulan pada penelitian ini adalah tidak terdapat hubungan antara kepatuhan pelaksanaan CP terhadap outcome  klinik dan total biaya riil pasien sectio cesaria, serta terdapat hubungan usia dan kelas perawatan terhadap total biaya riil pasien sectio caesaria.